Exposing Feminist, Orientalist Western Literary Portrayals of Islam and Muslims: From the Monstrous ‘Saracens’ to the Oppressed Muslim Women - El Fida, Brahim (Advances in Social Sciences Research Journal, 2023)
Orientalism and its legacies still exercise tremendous influence on how Arabs/Muslims, previously called ’Saracens,’ are perceived and represented in different Christian European, then American narratives and contexts. The Prophet Muhammad was targetdd to discredit him as ’false’ Prophet and and ’ambitious’ leader. The Images of sexual potency and debauchery was first addressed to Muhammad, and then trasferred to ’Turks’, Arabs and ’Moors’. The continuity of the very images hinder any sincere attempts at mutual understanding. These conceptions are reiterated and reproduced in political discourses and campaigns. They have a negative influence how Islam and Msulisms are conceived and treated.